Inhibition Effects of Culture Filtrates and Volatile Compounds of Antagonistic Microbes Isolated from Vermicompos and Compost Teas on the Growth of Alternaria solani Sor. in Vitro - Istifadah, Noor; Septiandini, Adelia; Hartati, Sri; Widiantini, Fitri (CROPSAVER, 2022)
Alternaria solani Sor. is one of destructive pathogens in solanaceous plants including tomato. Bacteria and yeast isolated from water extract of organic matters are potential as biological control agents of plant pathogenic fungi. Mechanisms of antagonism of bacteria and yeast can be through antibiosis. This study was conducted to examine the abilities of culture filtrate and volatile compounds produced by antagonistic bacteria and yeast isolated from compost and vermicompost teas to inhibit the growth of A. solani in vitro. The experiments were arranged in randomized complete design with four replications. The culture filtrate experiment applied well diffusion method, while the volatile compound effect experiment used petri dish sandwich method. The results showed that the culture filtrates of four bacteria and three yeast isolates inhibited the growth of A. solani in vitro by 16.6-87.5%. The highest inhibition level was showed by KSB4 isolate (Bacillus subtilis), a bacterial isolate from cow manure compost tea. In the volatile compound effect experiment, the tested bacteria and yeast isolates inhibited the pathogen growth by 31.3-75.2%, with the highest inhibition was showed by KcB3, a bacterial isolate from vermicompost tea. The isolate that its culture filtrate and volatile compounds both showed high inhibition level (62.7% and 87.5%) on A. solani growth was KSB4 isolate (B. subtilis).